DIGITAL PRODUCT INNOVATION AND FINTECH STRATEGY IN ISLAMIC BANKING: EVIDENCE FOR SUSTAINABLE SERVICE TRANSFORMATION - Ahmad Azim Aufaq; Mugiyati Mugiyati (Jurnal Ekonomi Manajemen Bisnis Syariah dan Teknologi, 2026)
Digital transformation is reshaping Islamic banking, while fintech intensifies competition in financial services. This study aims to analyze the role of fintech strategy in driving digital product innovation and sustainable service transformation in Islamic banking. The sample consists of selected scholarly articles, review papers, and relevant academic publications on Islamic banking, fintech strategy, digital product innovation, and service transformation. This study employs a descriptive qualitative approach using secondary data and qualitative content analysis. The findings indicate that fintech strategy serves as the institutional foundation for digital transformation, while digital product innovation acts as the strategic mechanism that translates digital orientation into customer-facing financial services. The study also finds that sustainable service transformation depends not only on technological readiness, but also on customer acceptance, trust, perceived usefulness, and service quality. In conclusion, sustainable transformation in Islamic banking can be achieved when fintech strategy, digital product innovation, and service transformation are managed as an integrated system.